Setubully Akprind: Integrasi Whistleblowing dalam Sistem Informasi Pelaporan Bullying di Institut Sains & Teknologi Akprind Yogyakarta - Erna Kumalasari Nurnawati; Muhammad Adji Pratama; Juniana Husna (Jurnal Dinamika Informatika, 2023)
Bullying in cyberspace, including against students, is common and much goes unreported. A system needs to be created, where someone who gets bullied reports it without worrying about being exposed to the public. Setubully Akprind Web is a web application for reporting and addressing bullying. This study analyzes and develops Setubully Web using the Whistleblowing approach and the Waterfall development model. The development method includes requirements analysis, system design, implementation, and testing. The testing results show that Setubully Web functions well and effectively addresses bullying. Key features such as Home, Complaints, Admin Dashboard, Officer Dashboard, and User Dashboard work effectively. User management, reporting, responses, categories, and user profiles can be efficiently managed. The development of Setubully Web incorporates the Whistleblowing concept, allowing for anonymous or public reporting of complaints or bullying incidents. It is hoped that the website can become an effective platform for reporting and overcoming bullying, creating a safe and comfortable environment for users in the Institut Sains & Teknologi Akprind Yogyakarta in particular, and on other campuses in general.